Integration of contact network and autonomous trolleybuses for improving the city's transport system - Mytko, Mykola; Burlaka, Serhii; Halushchak, Oleksandr; Halushchak, Dmytro; Zelinskyi, Viacheslav (Technology audit and production reserves, 2025)
The object of the study is the technical characteristics of autonomous trolleybuses and the systems that ensure their uninterrupted power supply. A key challenge is the dependence of conventional trolleybuses on contact networks, which limits their route versatility, complicates operations in historic city centers, bridge crossings, and regions with underdeveloped infrastructure. The article examines key technological aspects of autonomous trolleybuses, including types of charging stations (contact, inductive, with pantographs), charging efficiency, energy consumption, and autonomous range. Examples of the implementation of this technology in Ukraine are presented, along with an analysis of charging costs and energy characteristics for runs of 20–50 km. The prospects of using autonomous trolleybuses for optimizing the city transport network, reducing CO₂ emissions, and improving the quality of passenger service are emphasized. Calculations have been made of the energy required for a trolleybus to travel a distance of 20–50 km, taking into account the average energy consumption (1.2–2.0 kWh/km), charging station capacity (up to 100 kW,) and charging efficiency (0.9). Calculations have shown that for an autonomous trolleybus run of 30 km, 45 kWh of energy is required. Modern lithium-ion batteries and charging stations with a capacity of up to 100 kW provide a full charge in 30 minutes. Intermediate charging at stops minimizes contact infrastructure while maintaining transport system flexibility. Autonomous trolleybuses reduce dependence on contact networks, which is especially relevant for bridge crossings with complicated construction or maintenance and historic centers requiring architecture preservation without excess infrastructure. They also significantly reduce CO₂ emissions to promote ecological sustainability and improve urban air quality by lowering pollution and benefiting public health.